A Brief History of IL-1 and IL-1 Ra in Rheumatology - Dayer, Jean-Michel; Oliviero, Francesca; Punzi, Leonardo (Frontiers in Pharmacology, 2017)
The history of what, in 1979, was calledinterleukin-1(IL-1), orchestrator of leukocyte inter-communication, began many years before then, initially by the observation of fever induction via the endogenous pyrogen (EP) (1974) and then in rheumatology on the role in tissue destruction in rheumatoid diseases via the induction of collagenase and PGE2 in human synovial cells by a mononuclear cell factor (MCF) (1977). Since then, the family has exploded to presently 11 members as well as many membrane-bound and soluble receptor forms. The discovery of a natural IL-1 receptor antagonist (IL-Ra) in human biological fluids has highlighted the importance of IL-1 and IL-1Ra in human diseases. Evidence delineating its role in autoinflammatory syndromes and the elucidation of the macromolecular complex referred to as “inflammasome” have been instrumental to our understanding of the link with IL-1. At present, the IL-1blockade as therapeutic approach is crucial for many hereditary autoinflammatory diseases, as well as for adult-onset Still’s disease, crystal-induced arthropathies, certain skin diseases including neutrophil-triggered skin diseases, Behçet’s disease and deficiency of IL-1Ra and other rare fever syndromes. Its role is only marginally important in rheumatoid arthritis and is still under debate with regard to osteoarthritis, type 2 diabetes mellitus, cardiovascular diseases and cancer. This brief historical review focuses on some aspects of IL-1, mainly IL1ß and IL-Ra, in rheumatology. There are many excellent reviews focusing on the IL-1 family in general or with regard to specific diseases or biological discoveries.